Mother-to-Child Transmission of HIV Infection and Its Determinants among Exposed Infants on Care and Follow-Up in Dire Dawa City, Eastern Ethiopia - Wudineh, Fisseha (AIDS Res Treat, 2016)
Since the scale-up for prevention of mother-to-child transmission (PMTCT) services, rates of HIV infection among exposed infants have significantly declined. However, current achievements fell short of achieving the target sets. We investigated mother-to-child transmission (MTCT) of HIV infection and its determinants among HIV-exposed infants on care at Dilchora Referral Hospital in Dire Dawa City Administration. A retrospective institutional cohort study was conducted by reviewing follow-up records of HIV-exposed infants who were enrolled into care. Infants' HIV serostatus was the outcome measure of the study. Bivariate and multivariate logistic regressions were employed to identify significant determinants. Of the 382 HIV-exposed infants enrolled into care, 60 (15.7%) became HIV positive. Rural residence (AOR: 3.29; 95% CI: 1.40, 7.22), home delivery (AOR: 3.35; 95% CI: 1.58, 8.38), infant not receiving ARV prophylaxis at birth (AOR: 5.83; 95% CI: 2.84, 11.94), mixed feeding practices (AOR: 42.21; 95% CI: 8.31, 214.38), and mother-child pairs neither receiving ARV (AOR: 4.42; 95% CI: 2.01, 9.82) were significant independent determinants of MTCT of HIV infection. Our findings suggest additional efforts to intensify scale-up of PMTCT services in rural setting and improve institutional delivery and postnatal care for HIV positive mothers and proper follow-up for HIV-exposed infants.